2017
DOI: 10.1097/md.0000000000005908
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis in patients with pancreatic cancer

Abstract: Acute pancreatitis (AP) is a rare manifestation of pancreatic cancer (PC). The relationship between AP and PC remains less distinct.From January 2009 to November 2015, 47consecutive patients with PC who presented with AP were reviewed for this study. Clinical features, clinicopathologic variables, postoperative complications, and follow-up evaluations of patients were documented in detail from our database. In order to identify cutoff threshold time for surgery, receiver operating curve (ROC) was built accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…Mujicaet reported that the overall survival rates at six months and 12 months in PDAC patients who presented initially with AP were 51% (23 cases) and 28% (13 cases), respectively[16]. A recent study at our medical center reported a survival rate of 23.4%(11 cases) at one year in PDAC patients with AP[17]. Consistent with this report, our previous study found that AP was negatively correlated with both overall survival and early recurrence (within 12 mo).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mujicaet reported that the overall survival rates at six months and 12 months in PDAC patients who presented initially with AP were 51% (23 cases) and 28% (13 cases), respectively[16]. A recent study at our medical center reported a survival rate of 23.4%(11 cases) at one year in PDAC patients with AP[17]. Consistent with this report, our previous study found that AP was negatively correlated with both overall survival and early recurrence (within 12 mo).…”
Section: Discussionmentioning
confidence: 99%
“…Our group recently demonstrated that the short-term outcome of pancreatic cancer patients after surgery is adversely affected by AP[15]. Adverse effects of perioperative AP include delayed surgical treatment, longer hospital stay, higher cost of treatment and a reduced quality of life, and may be related to premature mortality[14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The frequency of AP in pancreatic cancer patient has been reported to vary from 6.8% to 13.8% and majority of patients present with mild AP. [4][5][6] The ductal adenocarcinoma causes AP by obstructing the main PD, producing ductal hypertension, and consequent leakage of enzymes. These patients are usually misdiagnosed and the underlying malignancy…”
Section: Discussionmentioning
confidence: 99%
“…is usually hidden because of various reasons such as diffuse pancreatic inflammation in AP could mask the underlying mass lesion or a small-sized obstructing tumor may be missed on cross-sectional imaging. [6,7] In these cases, FDG PET-CT or EUS may help in detection of small lesions as was in the index case. [6,8] Peripancreatic PA is usually formed due to injury to the peripancreatic artery either because of pancreatitis, trauma, percutaneous or endoscopic interventional procedures, or abdominal surgery, leading on to leakage of blood into the surrounding tissue and formation of a blood-formed cavity communicating with the damaged artery.…”
mentioning
confidence: 96%
See 1 more Smart Citation